Identifikasi Kandungan Fenfluramin Hidroklorida dalam Obat Tradisional Jamu Pelangsing Sediaan Padat Bentuk Serbuk yang Beredar di Wilayah Kota Singaraja - Putu Dewi Wirayani Giri (International Journal of Applied Chemistry Research, 2021)
Currently, many herbs contain medicinal chemicals (BKO). For slimming herbs, the indications included reducing hunger, and they were suspected of containing BKO in the form of fenfluramin hydrochloride. Fenfluramine hydrochloride has indications as an anorexia or anti-obesity drug. This drug works by suppressing or inhibiting the stimuli sent by certain receptors in the stomach and intestines to the satiety center in the brain. This research is a descriptive study that aims to determine the presence of fenfluramin hydrochloride in traditional medicine for slimming herbal medicine in solid powder form circulating in Singaraja City. The subject of this research was slimming herbal medicine in solid dosage form or powder form suspected of containing fenfluramine hydrochloride circulating in the Singaraja City area. The object of this research is to determine the content of fenfluramin hydrochloride, which is suspected to be present in the herbal slimming solid dosage form of the powder. The identification of fenfluramine hydrochloride was carried out by the Thin Layer Chromatography (TLC) method. The results showed that there were two samples of herbal medicine containing fenfluramin hydrochloride among five samples of herbal slimming solid preparations in powder form circulating in the Singaraja area.